Fire Safety and Security System in High-rise Buildings in Tangail Pourashava (Journal of Environmental Science and Natural Resources, 2017)
Fire safety and security system in high-rise buildings has been a significant issue from the last century. However, there are numerous provisions for safety measures from such fires and the magnitude and nature of the problem of this hazard has been unknown. This study identifies the location of high-rise buildings in Tangail pourashava through an extensive survey and then identifies the unique fire safety problems of those buildings and their associated fire risk. As it turns out, most of those buildings are highly vulnerable to fire risk due to lack of major fire fighting equipments and defiance of related laws and regulations. The study then addresses the means to provide fire safety in those buildings from both design and codes perspectives. It elaborates on the need to provide both building and occupant based protection to achieve the best results. It concludes with an overview of the special problems associated with high-rise buildings combined with specific use and occupancy-related requirements, employee training and response.J. Environ. Sci. & Natural Resources, 10(1): 33-40 2017